2004
DOI: 10.1128/cdli.11.1.56-62.2004
|View full text |Cite
|
Sign up to set email alerts
|

Important Role of P-Selectin for Leukocyte Recruitment, Hepatocellular Injury, and Apoptosis in Endotoxemic Mice

Abstract: Leukocyte recruitment in the liver includes a two-step procedure in which selectin-dependent leukocyte rolling is a prerequisite for subsequent CD18-dependent leukocyte firm adhesion in postsinusoidal venules. However, the roles of the individual selectins in leukocyte rolling and adhesion, hepatocellular injury, and apoptosis remain elusive. Therefore, we examined the pathophysiological role of P-, E-, and L-selectin in male C57BL/6 mice challenged with lipopolysaccharide (LPS) and D-galactosamine (Gal) by us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
67
1
1

Year Published

2006
2006
2013
2013

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 62 publications
(82 citation statements)
references
References 39 publications
13
67
1
1
Order By: Relevance
“…Our study did not address which stage in the transmigration process of leukocytes that P-selectin supports. However, a recent intravital microscopic study demonstrated that P-selectin supports LPS-induced leukocyte rolling in the liver (14), which helps explain our present findings showing that inhibition of P-selectin substantially blocks endotoxin-provoked accumulation of leukocytes in the extravascular space in the liver. Thus it appears that the recruitment process of leukocytes in the liver is similar to that observed in other organs.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…Our study did not address which stage in the transmigration process of leukocytes that P-selectin supports. However, a recent intravital microscopic study demonstrated that P-selectin supports LPS-induced leukocyte rolling in the liver (14), which helps explain our present findings showing that inhibition of P-selectin substantially blocks endotoxin-provoked accumulation of leukocytes in the extravascular space in the liver. Thus it appears that the recruitment process of leukocytes in the liver is similar to that observed in other organs.…”
Section: Discussionsupporting
confidence: 59%
“…The host response to endotoxin challenge provokes upregulation of specific endothelial cell adhesion molecules. Interestingly, it has been shown that P-selectin supports leukocyte rolling and lymphocyte function antigen-1 mediates firm adhesion of leukocytes in postsinusoidal venules in septic liver injury (14,15). Moreover, hepatic accumulation of leukocytes in response to endotoxin challenge is dependent on CXC chemokines, including macrophage inflammatory protein-2 (MIP-2) and cytokineinduced neutrophil chemoattractant (KC), which trigger tissue extravasation of leukocytes (16).…”
mentioning
confidence: 99%
“…The protein encoded by Bcl-2 gene has been implicated in prolongation of cell survival by blocking apoptosis and preventing hepatic IRI (42,43). Although the protective effect of the blockade of leukocyte-endothelial cell interaction on the induction of apoptosis has been reported in liver injury models (17,44,45), the exact mechanism remains unclear. Khandoga et al (45) reported that P-selectin KO mice prevented microvascular injury and apoptosis after hepatic warm I/R.…”
Section: Discussionmentioning
confidence: 98%
“…Up-regulation of a variety of adhesion molecules was evoked following the LPS stimulation, mediating different phases of leukocyte recruitment in microvessels, with L-selectin in leukocytes and E-selectin in endothelial cells [7,28,29] being involved in leukocyte rolling along vascular endothelium [7] , and CD11b/CD18 in leukocytes and ICAM-1 in endothelial cells implicated in firm adhesion of leukocytes to vascular wall [5,15,30,31] . The fact that compound Danshen injection did not display any effect on the LPS-induced leukocyte rolling implies that it might reduce leukocytes adhering to venular wall through its inhibitory effect on the expression of adhesion molecules either CD11b/CD18 in neutrophils or ICAM-1 in endothelial cells or both rather than selectins.…”
Section: Discussionmentioning
confidence: 99%